2017
DOI: 10.4314/jasem.v20i4.27
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the physico-chemical properties of produced water from oil producing well in the Niger Delta Area, Nigeria

Abstract: Physicochemical properties of produced water from oil producing well were conducted using standard methods (American standard for testing and materials). Samples were obtained at different periods within two months. Produced water comprises approximately 98% of the total volume of exploration and production (E&P) waste generated by the oil and gas industry. Results obtained; pH (7.90-8

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Similar observations were made in previous studies conducted in Rivers State, in Bayelsa State, and Delta States. 13,[21][22][23][24][25][26] Some studies have reported that at low alkaline levels, water pipes and fixtures corrode, thus leading to the release of potentially harmful metals like copper and lead from the plumbing system into the drinking water. This action alters the aesthetics and taste of water (bitter or metallic taste) and may erode the enamel of the teeth of members of the community who consume it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar observations were made in previous studies conducted in Rivers State, in Bayelsa State, and Delta States. 13,[21][22][23][24][25][26] Some studies have reported that at low alkaline levels, water pipes and fixtures corrode, thus leading to the release of potentially harmful metals like copper and lead from the plumbing system into the drinking water. This action alters the aesthetics and taste of water (bitter or metallic taste) and may erode the enamel of the teeth of members of the community who consume it.…”
Section: Discussionmentioning
confidence: 99%
“…Total petroleum hydrocarbons (TPH), polyaromatic hydrocarbons (PAH), total oil and grease concentrations. [13][14][15] This study analysed and compared the physicochemical of drinking water sources in high and low-crude oil-producing communities in the Niger Delta region of Nigeria to observe if water sources for drinking and domestic activities are contaminated only on heavily polluted sites alone or otherwise.…”
Section: Introductionmentioning
confidence: 99%
“…According to Amiri et al [26] the EC finds higher level correlation significance with many of the water quality parameters, like TDS, chlorides, total alkalinity, sulphates, total hardness and magnesium. Similarly, Chikwe et al [34] identified that all the parameters are more or less correlated with others in the correlation and regression study of the physiochemical parameters of ground water.…”
Section: Correlation Analysis Of Parametersmentioning
confidence: 92%
“…Basically, the total water consists of water in the cavities of the subsurface formations and injected water which has a dual purpose of enhancing the recovery of oil and gas and maintaining pressure in the reservoir [ 9 , 10 , 11 ]. For gas production wells, PW also consists of condensed water [ 12 , 13 ]. Inclusive of water, PW is also a complex mixture of soluble and insoluble high molecular weight hydrocarbons (aromatic and saturated), heavy metals, anions, and other impurities [ 14 ].…”
Section: Introductionmentioning
confidence: 99%